ANALISIS PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 DI DAERAH 3T (NUSA TENGGARA TIMUR) - Fajeri Arkiang (Jurnal Pendidikan, 2021)
The COVID-19 pandemic has forced the education system to undertake distance learning (PJJ). This incident is vulnerable to students in the Frontier, Outermost, and Disadvantaged (3T) areas because of the potential to lose their right to study. The purpose of this study is to provide an overview of online learning during the COVID-19 pandemic in the 3T area, especially in the province of East Nusa Tenggara. This study uses a descriptive content analysis study method. The analysis was carried out on international, national articles, books and similar sources related to the implementation of online learning during the pandemic. Virtual learning is a solution to activate teaching and learning activities even though educational institutions have implemented work from home, considering that time and place are at risk during this pandemic. However, this virtual learning technique is very important to evaluate, because internet network connection is one of the obstacles faced by students whose homes are difficult to access the internet, especially those students who live in rural, remote and disadvantaged areas.